دور القروض الفلاحية في تمويل وتطوير القطاع الفلاحي في الجزائر - قمداني, صفية حميدة; غويني, العربي (جامعة الوادي - University of Eloued, 2021)
الهدف الرئيسي من البحث هو ابراز أهمية تمويل القطاع الفلاحي في الجزائر عن طريق دراسة حالة على مستوى المديرية الجهوية لبنك الفلاحة والتنمية الريفية بولاية عنابة، حيث يعاني تمويل الفلاحة في الجزائر من نقص التنسيق والتماسك بين بنك الفلاحة ومديريات الخدمات الفلاحية؛ مما دفع للبحث عن ما سيسمح بتعبئة جميع الموارد الكافية لتحقيق الاستثمارات في القطاع الفلاحي، وكذلك اظهار الوسائل الكفيلة لترشيده، وقد تم التوصل إلى أن القروض الفلاحية تساهم بشكل معتبر في دعم المستثمرات الفلاحية ،كما تم استخلاص أن المنتوج الفلاحي الجزائري في ارتفاع متواصل بالتوازي مع زيادة حصيلة هذه القروض. The main objective of this research is to highlight the importance of financing the agricultural sector in Algeria through a case study of the regional direction of agricultural and rural development Bank (BADR)– Annaba, Where the agricultural financing in Algeria suffers from a lack of coordination between BADR Bank and the DSA, this have lead to search for what allows to mobilize adequate resources to achieve investments in agricultural sector and to demonstrate the means to rationalize these resources. The study concludes that the agricultural credits contribute to the growth of agricultural investments in a significant way, and that Algerian agricultural product is simultaneously increasing with the increased credits
The role of agricultural credits in financing and developing the agricultural sector in Algeria
مقال
Keywords: القطاع الفلاحي ; التمويل الفلاحي ; قرض الرفيق ; قرض التحدي